In vitro Selection of Synbiotics and in vivo Investigation of Growth Indices, Reproduction Performance, Survival, and Ovarian Cyp19α Gene Expression in Zebrafish Danio rerio - Zakariaee, Hamideh; Sudagar, Mohammad; Hosseini, Seyede Sedighe; Paknejad, Hamed; Baruah, Kartik (Frontiers in Microbiology, 2021)
In this study, we tested the compatibility of two extracts from the plant Jerusalem artichokes and button mushrooms with two different Lactobacillus probiotics (Lactobacillus acidophilus; La and Lactobacillus delbrueckii subsp. Bulgaricus; Lb) to develop a synbiotic formulation to improve the growth, survival, and reproductive performances of farmed fishes. Initially, we employed in vitro approach to monitor the growth of the probiotic lactobacilli in the presence of the different doses of the plant-based prebiotics, to select interesting combination(s) for further verification under in vivo conditions using zebrafish as a model. Results from the in vitro screening assay in the broth showed that both the probiotic species showed a preference for 50% mushroom extract as a source of prebiotic. A synbiotic formulation, developed with the selected combination of L. acidophilus, L. bulgaricus and 50% mushroom extract, showed a positive influence on the growth and reproductive performances of the zebrafish. Our findings also imply that the improvement in the reproductive indices was associated with the upregulation of a cyp19a gene. Overall results suggest that a combination of L. acidophilus, L. bulgaricus and mushroom extract can be considered as a potential synbiotic for the successful production of aquaculture species.